Phase Ib study of duligotuzumab (MEHD7945A) plus cisplatin/5‐fluorouracil or carboplatin/paclitaxel for first‐line treatment of recurrent/metastatic squamous cell carcinoma of the head and neck. Issue 24 (15th August 2016) - Jimeno, Antonio; Machiels, Jean‐Pascal; Wirth, Lori; Specenier, Pol; Seiwert, Tanguy Y.; Mardjuadi, Feby; Wang, Xiaodong; Kapp, Amy V.; Royer‐Joo, Stephanie; Penuel, Elicia; McCall, Bruce; Pirzkall, Andrea; et al.
Abstract : BACKGROUND: This open‐label, multicenter, phase Ib study assessed the safety and preliminary activity of duligotuzumab, a dual‐action antibody that blocks ligand binding to human epidermal growth factor receptor 3 (HER3) and epidermal growth factor receptor, in combination with chemotherapy, in the first‐line treatment of patients with recurrent/metastatic squamous cell cancer of the head and neck. METHODS: On day 1, duligotuzumab at a dose of 1650 mg intravenously was combined with cisplatin at a dose of 100 mg/m 2 and 5‐fluorouracil at a dose of 1000 mg/m 2 /day on days 1 to 4 in treatment arm A, or carboplatin (area under the curve, 6 mg/mL/min) and paclitaxel (at a dose of 200 mg/m 2 ) in treatment arm B. Up to 6 cycles (21 days/cycle) were followed by duligotuzumab maintenance until disease progression or intolerable toxicity occurred. RESULTS: Nine patients in arm A and 15 patients in arm B received a median of 6 cycles of chemotherapy, and a median of 11 cycles (arm A) and 9 cycles (arm B) of duligotuzumab. Dose‐limiting toxicities occurred in 3 patients in arm A and 1 patient in arm B. Grade ≥ 3 treatment‐related adverse events (graded according to graded according to National Cancer Institute Common Terminology Criteria for Adverse Events [version 4.0]) in ≥ 3 patients were neutropenia (5 patients), hypokalemia (4 patients), dehydration (3 patients), anemia (3 patients), and diarrhea (3 patients) in arm A, and neutropenia (8 patients), anemia (5 patients), febrile neutropenia (4 patients), leukopenia (3 patients), thrombocytopenia (3 patients), and hypomagnesemia (3 patients) in arm B. The chemotherapy dose was reduced in 19 of 24 patients. Sixteen patients (67%) demonstrated objective responses regardless of human papillomavirus status or neuregulin 1 ( NRG1 ) mRNA expression (arm A: 2 confirmed complete responses and 4 confirmed partial responses; arm B: 2 confirmed complete responses and 8 confirmed partial responses). CONCLUSIONS: Duligotuzumab in combination with cisplatin/5‐fluorouracil or carboplatin/paclitaxel demonstrated encouraging activity in patients with recurrent/metastatic squamous cell cancer of the head and neck; an association with increased frequency and severity of select adverse events relative to historical data was suggestive of the potentiation of chemotherapy‐related adverse events. Cancer 2016;122:3803–3811. © 2016 American Cancer Society. Abstract : Duligotuzumab (MEHD7945A), a novel dual‐action humanized immunoglobulin G1 monoclonal antibody that targets human epidermal growth factor 3 (HER3) and epidermal growth factor receptor, demonstrated encouraging activity in patients with recurrent/metastatic squamous cell cancer of the head and neck in combination with cisplatin/5‐fluorouracil or carboplatin/paclitaxel. An association with the increased frequency and severity of select adverse events relative to historical data was suggestive of the potentiation of chemotherapy‐related adverse events.